Preliminary characterization of a tentatively novel rumen bacterial species from the genus Treponema - Trkov, M; Accetto, T; Kostanjsek, R; Avgustin, G (Folia microbiologica, 2001)
A new spirochetal strain was isolated from the rumen of a black-and-white Holstein cow and preliminarily characterized. The sugar fermentation tests and morphological observations indicated this organism to be a member of a novel, as yet undescribed spirochetal rumen species. The small subunit ribosomal RNA genes were amplified and the PCR products were cut with the restriction endonucleases TaqI, DdeI, HhaI and Sau3AI. The comparison of the observed RFLP with the hypothetical fragment lengths of the computer analyzed 16S rRNA sequences from the type strains of the ruminal spirochetes Treponema bryantii and T. saccharophilum confirmed the tentative novel identification. Transmission electron microscopy showed that the bacterium has the typical spirochetal structures, i.e. the outer sheath, the protoplasmic cylinder and the axial filament (it is not yet clear how many flagella compose the filament). An additional extracellular structure was observed which appeared as an exocytoplasmic polar flagellum, approximately 2 microns long and protruding from one tip of the cell. The average size of the cells was 0.5 x 10-15 microns and the wavelengths and the amplitudes of the primary coils were 2.9 and 1.3 microns, respectively.
Keywords: bachor; DNA bakterií; geny rRNA; fermentace; Microscopy, Electron; Polymorphism, Restriction Fragment Length; Genes, rRNA; RNA ribozomální 16S; Rumen; zvířata; Culture Media; RNA, Ribosomal, 16S; kultivační média; Fermentation; DNA, Bacterial; Treponema; Cattle; skot; elektronová mikroskopie; Animals; polymorfismus délky restrikčních fragmentů